Sensitive interfaces for blind people in virtual visits inside unknown spaces. Issue 133 (January 2020) - Guerrón, Nancy E; Cobo, Antonio; Serrano Olmedo, José J; Martín, Carlos
Highlights: In-advance virtual visits aid blind people in the tasks of objects and structure recognition in unknown indoor spaces. Participants evaluated three sensitive interfaces: voice, beeps and gestures. The effectiveness, efficiency and usefulness of each one was evaluated using up to thirty virtual reality applications. The combination of three sensitive interfaces and a cognitive interface in virtual reality applications facilitated the construction of cognitive maps for people who are blind. Abstract: Virtual reality applications with sensitive interfaces for blind users were developed and tested on smart mobiles running Android as operating system with the participation of twenty blind adults; each application was built with a cognitive interface and a combination of three sensitive interfaces (voice, beeps and gestures) to allow the user to explore the inside of a virtual scenario beforehand. The vibration was an extra, fixed sensitive interface that informed the user that the avatar was walking through the virtual world. The combination of different interfaces within the applications allowed to (1) provide multisensory information to the user while exploring an unknown virtual scenario, (2) build a model of the space in which the user is located and (3) successfully perform tasks in the real world. This research compared different patterns for each interface: 3 for voice, 3 for the beep and 4 for gestures, during the exploration of an unknown space, with the goal of determining which ones were the most efficient and effective at detecting, identifying and locating structures and objects in an unfamiliar environment, aiding blind users to develop a cognitive map of the explored place and successfully perform tasks within the real scenario. Evidence shows that the voice interface provides a statistically significant difference on effectiveness, efficiency, and cognitive mapping compared to other interfaces. Most decisively, pairwise comparisons have shown that, when compared to a normal speech rate, a speech rate 2 times faster manifested an improvement of 5.9% on object and structures detection, a reduction on exploration time of 39.72%, an improvement of 6% on quality of cognitive map development and greater success in carrying out the absolute tasks. The beep interface with 500 Hz frequency and 100 milliseconds spacing provided a statistically significant difference for cognitive mapping, showing an improvement of 8.9%. Finally, in the context of gesture interfaces, a single touch plus vertical swiping, produced statistically significant differences in the reduction of discovery time by 34.28%. Graphical abstract: Image, graphical abstract